2007
DOI: 10.1002/ijc.22852
|View full text |Cite
|
Sign up to set email alerts
|

Expression of coxsackie and adenovirus receptor reduces the lung metastatic potential of murine tumor cells

Abstract: The coxsackie and adenovirus receptor (CAR) is involved in the epithelial cell tight junction, the downregulated expression of which is observed in different cancer types. In the present study, we examined CAR's role in tumor metastasis using a B16 melanoma and CT26 colon adenocarcinoma model of experimental metastasis. In lung metastasis, the colony number of B16 cells stably expressing CAR (B16CAR) was significantly lower than that of the control CAR-negative B16 cells. B16 and CT26 cells transiently express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
35
0
2

Year Published

2008
2008
2012
2012

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(38 citation statements)
references
References 28 publications
1
35
0
2
Order By: Relevance
“…Similarly, when compared with normal prostate, CAR expression decreased in prostate carcinoma specimens of all Gleason scores [37] . Yamashita et al reported that CAR expression signifi cantly decreased the lung metastatic potential of B16 melanoma cells in lung after IV injection and in the migration in murine model [38] . Here, we systematically analyzed CAR expression in a large number of lung cancer specimens with RT-PCR, immunohistochemistry and Western blot analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, when compared with normal prostate, CAR expression decreased in prostate carcinoma specimens of all Gleason scores [37] . Yamashita et al reported that CAR expression signifi cantly decreased the lung metastatic potential of B16 melanoma cells in lung after IV injection and in the migration in murine model [38] . Here, we systematically analyzed CAR expression in a large number of lung cancer specimens with RT-PCR, immunohistochemistry and Western blot analysis.…”
Section: Discussionmentioning
confidence: 99%
“…For example, because many tumor cells, including melanoma, that are targets for gene therapy express no or little CAR, it is difficult to achieve sufficient gene expression and therapeutic effect (Okada et al, 2003b;Mathis et al, 2006). Reduced expression of CAR in advanced tumor stages is one of the major obstacles to the use of Adv for cancer gene therapy (Yamamoto et al, 1997;Li et al, 1999;Yamashita et al, 2007). To overcome these problems, we developed Tat-modified Adv with broadened tropism and enhanced transduction efficiency.…”
Section: Discussionmentioning
confidence: 99%
“…30 As many tumor cells that are targets for gene therapy, including melanoma cells, express no or little CAR, it is difficult to achieve sufficient gene expression for a therapeutic effect. [31][32][33] Importantly, PEG-Ad-TERT/ HSVtk induced significant therapeutic effects against metastatic B16BL6 and CT26.CL25 cells, which are CARnegative cells, 34 whereas PEG[20K/45%]-Ad showed significantly reduced CAR-dependent transgene expression in vitro compared with unmodified Adv, because the interaction of Adv and CAR was inhibited by the steric hindrance of PEG chains. 35 As the nonspecific endocytotic activity of tumor tissue is enhanced in general compared with that of normal tissue, we think that the accumulation and retention of PEG[20K/45%]-Ad in the tumor tissue induced its efficient uptake.…”
Section: Discussionmentioning
confidence: 99%